Africa on the Verge of a Linguistic Genocide: The Need for Action - Ugwu, Eucharia Okwudilichukwu (European Scientific Journal, ESJ, 2019)
Linguistic diversity is one of the rich endowments of the African continent. Language has a lot of potential benefits to the world at large and, most especially, to the people who speak it. However, in the present globalised world, language endangerment has become a stark reality as many world languages threaten the survival of the weaker ones spoken by the numerous indigenous people. In this mere linguistic warfare which the world has been plunged into, languages that are well-developed and have more speakers have greater chances of surviving. Due to the large number of languages in Africa, it may appear, on the periphery, asthough these languages are safe. However, available statistics shows that the wave of language endangerment is already sweeping through the continent, as a result of which many African languages have gone into extinction and many are heading towardsthe same fate, unless a drastic action is taken. No part of Africa is safe and almost all African languages are threatened to some degree. This paper exposes the conditions of African indigenous languages and the need for actions to be taken to avert linguistic genocide in the continent.